Tibetan peach pie : a true account of an imaginative life - Robbins, Tom, 1932- (Ecco, an imprint of HarperCollinsPublishers, 2014)
Internationally bestselling novelist and American icon Tom Robbins delivers the long awaited tale of his wild life and times, both at home and around the globe.